Origin and Use of Hydroxyl Group Tolerance in Cationic Molybdenum Imido Alkylidene N‐Heterocyclic Carbene Catalysts - Schowner, Roman (Angew Chem Int Ed Engl, 2019)
The origin of hydroxyl group tolerance in neutral and especially cationic molybdenum imido alkylidene N‐heterocyclic carbene (NHC) complexes has been investigated. A wide range of catalysts was prepared and tested. Most cationic complexes can be handled in air without difficulty and display an unprecedented stability towards water and alcohols. NHC complexes were successfully used with substrates containing the hydroxyl functionality in acyclic diene metathesis polymerization, homo‐, cross and ring‐opening cross metathesis reactions. The catalysts remain active even in 2‐PrOH and are applicable in ring‐opening metathesis polymerization and alkene homometathesis using alcohols as solvent. The use of weakly basic bidentate, hemilabile anionic ligands such as triflate or pentafluorobenzoate and weakly basic aromatic imido ligands in combination with a sterically demanding 1,3‐dimesitylimidazol‐2‐ylidene NHC ligand was found essential for reactive and yet robust catalysts.